Dietary quality influences body composition in overweight and obese pregnant women - Outi Pellonperä; Ella Koivuniemi; Tero Vahlberg; Kati Mokkala; Kristiina Tertti; Tapani Rönnemaa; Kirsi Laitinen (Churchill Livingstone, 2022)
BACKGROUND & AIMS:
Excessive adiposity and gestational weight gain (GWG) have been linked with maternal and offspring morbidity. We investigated the relation of maternal diet, physical activity and GWG on body composition in overweight and obese pregnant women.
METHODS:
Fat mass (FM) and fat free mass (FFM) of 110 overweight and obese pregnant women were measured by air displacement plethysmography in early and late pregnancy (mean 13.5 and 35.3 gestational weeks). At the same time points, the quality of overall diet was assessed by validated index of diet quality (IDQ) questionnaire (score < 10/15 denotes poor dietary quality and score ≥ 10/15 denotes good dietary quality), nutrient intakes by 3-day food diaries, and physical activity by questionnaire. Weight gain between early and late pregnancy was compared to the gestational weight gain guidelines issued by Institute of Medicine.
RESULTS:
Of the women, 77% gained more weight than recommended; this was related to greater dietary fat consumption (80 ± 21 g/day vs. 67 ± 11 g/day, p = 0.010) and greater increase in FM (2.7 ± 3.0 kg vs. -1.0 ± 2.4 kg, p < 0.001) compared to women with ideal GWG. Dietary protein intake (g) correlated positively with FFM at both time points (early pregnancy: r = 0.31, p < 0.002, late pregnancy: r = 0.39, p < 0.001). Women with higher dietary quality index score had more FFM, compared to women with lower dietary quality (early pregnancy FFM: 48.8 ± 5.8 kg vs. 45.8 ± 4.7 kg, p = 0.004, late pregnancy FFM: 56.1 ± 6.4 kg vs. 53.4 ± 5.6 kg, p = 0.025). No correlations were detected between total energy intake or physical activity and FM or FFM at early or late pregnancy.
CONCLUSIONS:
Body composition changes from early to late pregnancy were related to the amount of weight gained and overall dietary quality during pregnancy. Higher dietary quality and protein intake were associated with greater FFM, while dietary fat intake was related to excess weight gain. Identification of these dietary determinants of body composition and weight offers new targets for dietary counseling of pregnant women and thus potential for ensuing health benefits through reduced adiposity.